2018
DOI: 10.1016/j.biocel.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of threonine residues on Shc promotes ligand binding and mediates crosstalk between MAPK and Akt pathways in breast cancer cells

Abstract: Scaffold proteins play important roles in regulating signalling network fidelity, the absence of which is often the basis for diseases such as cancer. In the present work, we show that the prototypical scaffold protein Shc is phosphorylated by the extracellular signal-regulated kinase, Erk. In addition, Shc threonine phosphorylation is specifically up-regulated in two selected triple-negative breast cancer (TNBC) cell lines. To explore how Erk-mediated threonine phosphorylation on Shc might play a role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…Notably however, the pathways connecting SHC to PI3K, that are indicated by our current observations, remain unknown. Although several studies have suggested a complex formation occurs between SHC and PI3K via the 14-3-3 protein (Ursini-Siegel et al, 2012;Suen et al, 2018), it is not certain whether this underpinned any of our present findings. PI3K is one of the effectors of RAS (Vivanco and Sawyers, 2002;Castellano and Downward, 2011).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Notably however, the pathways connecting SHC to PI3K, that are indicated by our current observations, remain unknown. Although several studies have suggested a complex formation occurs between SHC and PI3K via the 14-3-3 protein (Ursini-Siegel et al, 2012;Suen et al, 2018), it is not certain whether this underpinned any of our present findings. PI3K is one of the effectors of RAS (Vivanco and Sawyers, 2002;Castellano and Downward, 2011).…”
Section: Discussioncontrasting
confidence: 53%
“…It has been reported also that SHC is required for the full activation of RAS/MAPK signaling when cells are stimulated with growth factors at a low concentration (Lai and Pawson, 2000). In addition, SHC interacts with the complex of 14-3-3 and PI3K for activation of the RAS/MAPK and PI3K/AKT signaling pathways (Ursini-Siegel et al, 2012;Suen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids and acetate in cancers can be used as nutritional supports for protein synthesis and lipid metabolism, respectively. Threonine was reported to be responsible for Akt and ERK signalling pathway in breast cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the recruitment of PTP-PEST depends on Serine 29 phosphorylation to stabilize ShcA/PTP-PEST interactions. Moreover, Threonine 214 phosphorylation of ShcA was recently shown to increase ERK and AKT activation (49). Thus, serine/threonine phosphorylation of ShcA dynamically regulates the signaling potential of the adaptor protein, yet it is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%